Parent Education Program about Dental Health Education for Intellectual Disability Children in Wetland - Renie Kumala Dewi; Beta Widya Oktiani; Anugrah Qatrunnada Hakim; Ika Kusuma Wardani (Green Publisher Indonesia, 2023)
Background: Wetlands are swamps with a water pH of 3.5-4.5. There are also cariogenic bacteria, including Streptococcus sp. Parents living in wetlands have a habit of using wetland water for their daily routine, such as for gargling after toothbrushing. Oral health problems in intellectual disabilities children include gingivitis, periodontitis, and rapid dental caries. Dental Health Education can increase the awareness of people in wetlands. Purpose: to analyse the effectivity of parent education program about dental health education for intellectual disability children in Wetland Methods: A quasi-experiment study with pretest and posttest without control design that used a simple random sampling technique. Results: Thirty-eight parents of intellectual disabilities children filled questionnaires for pretest, then asked to watch an animated video of Dental Health Education for moderate intellectual disabilities children living in wetlands concerning dental caries prevention. As for the posttest, the samples were asked to fill the same questionnaire after 20 days. Data were analyzed using Wilcoxon statistical test. The results of the Wilcoxon test prove value = 0.000 (p < 0.05). Conclusion: There is an effect of the parent education program through Dental Health Education video for intellectual disabilities children in wetlands on dental caries prevention. This video can be applied to parents of children with intellectual disabilities as promotive action for dental health education.